Pola Komunikasi Organisasi Mahasiswa dan Implementasi Kerja di HMJ UIN Sumatra Utara - Nawaf, Azmi; Sikumbang, Ahmad Tamrin (Universitas Islam Tribakti Lirboyo Kediri, 2024)
This research discusses issues related to Communication Patterns of Student Organizations and Work Implementation in the Student Organization (HMJ) UIN North Sumatra. Effective communication between administrators greatly affects organizational performance. The purpose of this study is to explore the dynamics of communication in organizations. The role of communication in question shows the success of leadership in the organization in increasing work motivation by forming an organizational structure that has a communication style that is characterized as a liaison between organizational members, so that there is no jealousy and gaps between position holders. The role of communication is the object of study in this research which is part of organizational behavior in organizational work motivation. The methodology used in this research is descriptive research through a qualitative approach which is carried out through writing systematic, actual, and accurate descriptions containing facts and relationships related to the phenomena that occur. The data collection techniques used include questionnaires, interviews, observations, and documentation, as well as analyzing communication patterns and their influence on the implementation of organizational work programs.The results showed that effective communication patterns play an important role in the implementation of the organization's work program. This finding was obtained from data analysis that showed a positive correlation between good communication and the level of efficiency and effectiveness of organizational management. Factors such as openness, clarity of information, and frequency of communication were shown to contribute significantly to organizational performance. This research provides practical guidance for the management of the Student Association of the Department of Communication Science of the State University of North Sumatra to improve their communication patterns. By implementing more effective communication, it is expected that organizations can achieve their goals more efficiently and effectively.